Ruthenium-based olefin metathesis catalysts with monodentate unsymmetrical NHC ligands - Paradiso, Veronica; Costabile, Chiara; Grisi, Fabia (Beilstein Journal of Organic Chemistry, 2018)
An overview on the catalytic properties of ruthenium complexes for olefin metathesis bearing monodentate unsymmetrical N-heterocyclic diaminocarbene ligands is provided. The non-symmetric nature of these NHC architectures strongly influences activity and selectivity of the resulting catalysts. The main achievements that have been accomplished in significant areas of olefin metathesis up to the current state of research are discussed.
Keywords: ligand design; olefin metathesis; ruthenium catalysts; selectivity; unsymmetrical N-heterocyclic carbenes